The NGO’s impact on São Tomé e Príncipe’s sustainable development - Miranda, Joana Neto da Silva (2021)
Non-Governmental Organizations (NGO) have an important role in the development of societies and communities and in the promotion of citizens engagement towards a fairer world. Assessing the development and the quality of life of people and countries should be based on a perspective that goes beyond economic indicators, and sustainable development (SD) has to be seriously assumed. Understanding the impact of NGO in the SD of developing countries is not a simple challenge; it implies the use of several concepts, such as SD, education, economic development and poverty. This thesis studies the impact of NGO in SD focusing on a particular African country - STP. Based on a review of fundamental concepts, a methodology was defined and applied, aimed to evaluate indicators of the SD goals. The specific case of the NGO MOVE in STP was worked using results from questionnaires to entrepreneurs. A main, and in some way expected, conclusion is that data is not enough to allow a clear analysis. Anyway, the available data indicates that NGO are impacting the SD of the country, namely regarding healthy lives and well-being, quality education and lifelong learning opportunities. Nevertheless, this impact could be higher and better. Thus, and to promote more efficiency, it is recommended to properly monitor, register and analyse the work developed by NGO. It is also suggested that NGO, government and other institutions and entities should more frequently work together and combine efforts in order to achieve a stronger evolution towards sustainable development.